A Multi-Layered Ring Under Parabolic Pressure - MARKIDES, Christos F.; PASIOU, Ermioni D.; KOURKOULIS, Stavros K. (Engineering Transactions, 2016)
The stress- and displacement-fields developed in a circular ring consisting of a finite number of linearly elastic homo¬geneous and isotropic concentric layers are determined. The composite ring is subjected to a distribution of radial stresses (acting along two finite arcs of its periphery) varying according to a parabolic law. The problem is solved analytically adopting Savin’s approach for an infinite plate with a hole strengthened by rings. Taking advantage of the analytic solution, a numerical model is properly calibrated and validated by considering the case of a three-layered ring. It is concluded that the constructed model simulates reality in an excellent manner and therefore it can be safely used for a thorough parametric analysis of the numerous factors influencing the stress- and displacement-fields.